Pengaruh DosisPupukKandangAyamdan Air KelapaterhadapPertumbuhandanProduksiTanamanKacangHijau (Vignaradiata L.) di Tanah Alluvial - Pambajeng, Ratu Sekar Annisa; Amri, Al Ichsan; Irfandri, Irfandri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the effects of chicken manure and coconut water fertilizer on the growth and production of green bean plants (Vigna radiata L.) in alluvial soil. The design of this experiment was Completely Randomized Design (CRD) which consist of 2 factors; The dose of chicken manure (A) and consisting of four levels: (A0) without the dose of chicken manure, (A1) Chicken manure dose of 15 tons.ha-1 (60 g.polybag-1), (A2) Chicken manure with dose of 17.5 tons.ha-1 (70 g.polybag-1), (A3) Chicken manure dose of 20 tons.ha-1 (80 g.polybag-1) and; Coconut water concentration (K) which consist of three levels, i.e: (K1) coconut water concentration of 50%, (K2) coconut water concentration of 75%, and (K3) coconut water concentration of 100%. The parameters observed were plant height, flowers age, hervest age, the number of root nodules per plant, number of seeds per pod, total number of pods per plant, and weight of 100 dried seeds. The result of this experiment that the dose of chicken manure and coconut water gave no significant effect on the growth and production of green bean plants (Vigna radiata L.) in alluvial soils. Key Words:Green Bean, Dose of Chicken Manure, Coconut Water.